2021
DOI: 10.3390/ijerph182111485
|View full text |Cite
|
Sign up to set email alerts
|

Australia’s Disability Employment Services Program: Participant Perspectives on Factors Influencing Access to Work

Abstract: Disability employment programs play a key role in supporting people with disability to overcome barriers to finding and maintaining work. Despite significant investment, ongoing reforms to Australia’s Disability Employment Services (DES) are yet to lead to improved outcomes. This paper presents findings from the Improving Disability Employment Study (IDES): a two-wave survey of 197 DES participants that aims to understand their perspectives on factors that influence access to paid work. Analysis of employment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…First, given the high unemployment rate among autistic individuals in this study (52%), participants may have been more likely to rate DES providers negatively. This finding is similar to (Devine et al, 2021 ) who reported that unemployed individuals experienced more employment barriers and wished for more vocational provider support. Notwithstanding this, approximately 25% of all data were collected during the first wave of the COVID-19 pandemic which may also have impacted reported employment rates and subsequent ratings of DES providers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…First, given the high unemployment rate among autistic individuals in this study (52%), participants may have been more likely to rate DES providers negatively. This finding is similar to (Devine et al, 2021 ) who reported that unemployed individuals experienced more employment barriers and wished for more vocational provider support. Notwithstanding this, approximately 25% of all data were collected during the first wave of the COVID-19 pandemic which may also have impacted reported employment rates and subsequent ratings of DES providers.…”
Section: Discussionsupporting
confidence: 90%
“…Perhaps supporting this finding is that many of the autistic jobseekers in this research had achieved post-secondary qualifications. The lack of such qualifications is typically a barrier to employment (Ohl et al, 2017), so too for people with other disability types (Devine et al, 2021). Yet, most autistic people in this study had not been assisted into employment by a DES provider despite the majority having obtained further education.…”
Section: The Autistic Jobseekermentioning
confidence: 99%
“…The inclusion of social support in mental health delivery is important in achieving favourable outcomes, with family and friends often providing broader connections for the person (Coffey et al, 2019), and specifically, key support in the employment process (Fossey & Harvey, 2010). In the Australian context, Devine et al (2021) conducted a survey with Disability Employment Service (DES) participants to explore their perceptions of factors impacting on access to employment. Importantly, participants reported that they were more likely to gain employment via connections with family and friends than with assistance from their employment service, with lack of family help experienced as a barrier to finding and maintaining employment (Devine et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the Australian context, Devine et al (2021) conducted a survey with Disability Employment Service (DES) participants to explore their perceptions of factors impacting on access to employment. Importantly, participants reported that they were more likely to gain employment via connections with family and friends than with assistance from their employment service, with lack of family help experienced as a barrier to finding and maintaining employment (Devine et al, 2021). Furthermore, a recent RCT of an IPS program found that social and emotional support were key predictors of employment at the 18‐month follow‐up (Fyhn et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…First, providers appointed to partnerships included both government and insurance-funded service providers, with some differences between the two service models. The Australian Government Disability Employment Service (DES) program funds generalist disability providers to provide employment services for people with disability [ 29 ]. DES providers rarely employ allied health professionals to undertake assessments and guide vocational goal setting.…”
Section: Introductionmentioning
confidence: 99%